Pharmaceutical preparations and illicit drugs as contaminating substances of surface and wastewater - Miloš B. Rajković; Milica Lučić (Zaštita Materijala, 2018)
The presence of pharmaceuticals and narcotic drugs in waste, surface and groundwater presents a serious problem for human health. The reason for this is the fact that these compounds possess biological activity, they have easy mobility, some of them have the ability to bioaccumulation and many are heavily biodegradable. So far, researches have shown that the main source for pharmaceutical preparations in water are municipal waste water with origin from households, hospitals and industry. The main drugs which appear in waters are: analgesics and anti-inflammatory compounds, antibiotics, β-blockers, hormones, lipid regulators, cytostatics, contrast remedy, drugs and disinfection remedies. The composition of products for personal hygiene and cosmetics includes compounds that possess the ability of bioaccumulation, where many of them show estrogen and endocrine effects. Examination of waste waters in Western Balkan cities indicate that drugs are mostly consumed in Zagreb, Belgrade and Novi Sad (cocaine, amphetamine and MDMA). A trend of increasing drug usage on weekends was observed on average of 10-20%. Main processes that determine future usage of drugs in water environments are biotransformation, sorption, chemical transformation, phototransformation and evaporation.